2021
DOI: 10.1039/d1cp04614d
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical studies of the gas-phase reactions of O(1D) with H2O and D2O at low temperature

Abstract: Measurements of the O(1D) + H2O, D2O reactions show that these processes become much more rapid below 100 K.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Given that the RPMD method is exact at high temperatures (see, for instance, ref. 48–50 and 53–57), this agreement is indirect evidence of the quality of PES-2023. In the CVT method, the recrossing effect is evaluated as the ratio between CVT ( s = s *) and TST ( s = 0, saddle point) rate constants, i.e.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Given that the RPMD method is exact at high temperatures (see, for instance, ref. 48–50 and 53–57), this agreement is indirect evidence of the quality of PES-2023. In the CVT method, the recrossing effect is evaluated as the ratio between CVT ( s = s *) and TST ( s = 0, saddle point) rate constants, i.e.…”
Section: Resultsmentioning
confidence: 65%
“…Previous studies have shown that the RPMD method can efficiently take account of the quantum effects, such as the ZPE and tunnelling, along the reaction pathway. 49,50 The RPMDrate input parameters are summarized in Table 2.…”
Section: Pccp Papermentioning
confidence: 99%
“…The original apparatus as described has been modified over the years to incorporate a tunable narrow-band VUV source for detection purposes. In this way, it has been possible to study the low-temperature reactivity of several atomic radicals such as C­( 3 P), , O­( 1 D), , N­( 2 D), , and C­( 1 D) [indirectly through product H­( 2 S) formation] , by exciting electronic transitions of these species in the 115–130 nm wavelength range. Despite the availability of Laval nozzles based on several different carrier gases including N 2 , SF 6 , and Ar, the present experiments were restricted to using argon-type nozzles as the rate constants for O­( 1 D) quenching by Ar are small enough (6–7 × 10 –13 cm 3 s –1 ) to allow kinetic measurements to be performed. , Indeed, N 2 is known to rapidly quench O­( 1 D) atoms at room temperature and below. , Three different nozzles were employed here, providing supersonic flows with characteristic temperatures of 127, 75, and 50 K with Ar as the carrier gas.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Mechanistically at room temperature and below, O( 1 D) atoms react with organic molecules predominantly by insertion into C-H and O-H bonds, forming long-lived intermediates such as CH3OH during the O( 1 D) + CH4 reaction and H2O2 during the O( 1 D) + H2O reaction before dissociating. 17,18,19,20,21 When CH3OH is employed as the coreagent species, as a bifunctional molecule two possibilities present themselves for the insertion process. Here, O( 1 D) can insert into either one of the C-H bonds of the CH3 moiety or into the O-H bond itself, leading to the possible formation of two distinct intermediate species, HOCH2OH following C-H insertion or CH3OOH formation following O-H insertion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation